Correction: Osmium isotope analysis as an innovative tool for provenancing ancient iron: A systematic approach. - Michael Brauns; Naama Yahalom-Mack; Ivan Stepanov; Lee Sauder; Jake Keen; Adi Eliyahu-Behar (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0229623.].